USE OF VISUALIZATION TECHNOLOGIES IN DISTANCE LEARNING OF THE UKRAINIAN LANGUAGE IN INSTITUTIONS OF GENERAL SECONDARY EDUCATION - Natalia Dyka; Oleksandra Glazova (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article highlights the features of the use of visualization technologies during distance learning of the Ukrainian language in general secondary education. Scientific works on the coverage of the outlined problem in them are analyzed. It is proved that an effective learning tool, a productive methodological tool for intellectual development of students is the visualization of educational material. The peculiarities of the preparation of educational information are determined, which in a visually accessible for perception and understanding form can provide students with basic or necessary information. It is emphasized that the principle of cognitive visualization is based on psychological laws, according to which the effectiveness of learning increases through the connection to the process of perception of the «figurative» right hemisphere. The peculiarities of using the technology of visualization of educational material, in particular in distance learning, are substantiated. Techniques of structuring and visualization of educational material are described. Emphasis is placed on compliance with certain recommendations to achieve the goals set in the implementation of visualization technologies. It is emphasized that when working on the visualization of educational material, it is necessary to take into account certain patterns of perception of visual aids by students. The typical mistakes that are most often made in the process of visualization of educational material are analyzed, recommendations are given to eliminate them. It was found that the use of distance and blended learning and the significant potential of multimedia learning tools encourage teachers to use visualization in the educational process, which contributes to the intensification of the process of learning. Examples of realization of various pedagogical technologies of visualization in the process of teaching the Ukrainian language in general secondary education institutions in a distance format are given.